Insufficient Protein Intake Is Associated With Increased Mortality in 630 Patients With Cirrhosis Awaiting Liver Transplantation. (9th February 2015) - Ney, Michael; Abraldes, Juan G.; Ma, Mang; Belland, Dawn; Harvey, Andrea; Robbins, Sarah; Den Heyer, Vanessa; Tandon, Puneeta
Abstract : Background: For patients awaiting liver transplantation, we aimed to determine the prevalence and predictors of insufficient protein intake as well as to determine whether very low protein intake was an independent predictor of malnutrition and mortality. Materials and Methods : Adults with cirrhosis who were activated on our local liver transplant waiting list between January 2000 and October 2009 were included. Estimated protein intake was derived from dietary records. Patients with incomplete dietary records were excluded. Multivariable logistic regression and competing risk analysis were used. Results : Of 742 potential patients, 112 were excluded due to insufficient data, leaving 630 patients for evaluation. Mean protein intake was 1.0 ± 0.36 g/kg/d and only 24% of patients met the expert consensus recommended threshold of > 1.2 g/kg of protein per day. Very low protein intake (< 0.8 g/kg/d) was associated with worse liver disease severity (as measured by Child‐Pugh or MELD). Protein intake below 0.8 g/kg/d was an independent predictor both of malnutrition as measured by the subjective global assessment (adjusted odds ratio [95% confidence interval (CI)]: 2.0 [1.3–3.0]) and of transplant waiting list mortality (adjusted hazard ratio [95% CI]: 1.8 [1.2–2.7]). Conclusion : In this large cohort of liver transplant waitlisted patients, very low protein intake was prevalent and independently associated with malnutrition and mortality. Unlike many other prognostic factors, protein intake is potentially modifiable. Prospective studies are warranted to evaluate the effect of targeted protein repletion on clinically relevant outcomes such as muscle mass, muscle function, immune function, and mortality.